Improving Consumer Satisfaction with Cimory on the Valley in Terms of Product Differentiation, Brand Image, and Service - Nadira Oktha Henry Utami; Githa Febiola; Iwin Arnova; Helmi Herawati (Sharia Economic and Management Business Journal (SEMBJ), 2024)
This article discusses increasing consumer satisfaction with cimory on the valley through product differentiation, brand image and service. This research aims to explore how these factors contribute to consumer perceptions of cimory on the valley. Through in-depth analysis, this research highlights the importance of unique product differentiation, strong brand image, and quality service in influencing consumer satisfaction. It is hoped that the results of this research will provide valuable insights for cimory on the valley businesses to improve consumer experience and strengthen their brand position in the market.